STUDI FENOMENOLOGI DAN ANALISIS DRAMATURGI PENGALAMAN HIDUP PADA SISWA SMA NEGERI 17 BATAM PENGGUNAAN SECOND ACCOUNT INSTAGRAM: PENDAHULUAN, KAJIAN TEORI, METODOLOGI PENELITIAN, HASIL DAN PEMBAHASAN, SIMPULAN, DAFTAR PUSTAKA - Novelia, Bella; Rorong, Michael Jibrael (LPPM Universitas Putera Batam, 2024)
Adolescents are among the most widely associated with technological development. Adolescence becomes a time when a person who is on a violent rampage searches for their identity and their experiences. It also leads to where many teenagers easily follow things done by others such as forming a good self-image, they want to be admired, they want to gain recognition by the public, and they want to show their existence through the experiences they feel. It's the same with the 17 Batam Negeri High School students who have an Instagram account. For some students, not only using Instagram as a medium to share information and communications, but also making Instagram a place to share experiences and a place to complain. There is even one student who has 2 Instagram accounts. The purpose of this study is to analyze and know the experiences, shapes, patterns, activities, and how Frontstage and Backstage users second account on 17 Batam State High School students. This study uses qualitative methods with phenomenological approaches, which are based on a person's subjective or phenomenological experience and use Dramatic analysis (as a theory). The results of this study are how communication experiences, forms and patterns of communication, communication activities, as well as Front stage and Back stage on users of 17 Batam State High School students' seccond accounts.